Multiterminal Conductance of a Floquet Topological Insulator - Foa Torres, Luis Eduardo Francisco (2014)
We report on simulations of the dc conductance and quantum Hall response of a Floquet topologicalinsulator using Floquet scattering theory. Our results reveal that laser-induced edge states lead to quantumHall plateaus once imperfect matching with the nonilluminated leads is lessened. The magnitude of the Hallplateaus, however, is not directly related to the number and chirality of all the edge states at a given energy,as usual. Instead, the plateaus are dominated by those edge states adding to the time-averaged density ofstates. Therefore, the dc quantum Hall conductance of a Floquet topological insulator is not directly linkedto topological invariants of the full Floquet bands.